Penerapan Model Pembelajaran Word Square untuk Meningkatkan Hasil Belajar Ekonomi Siswa Kelas X SMA Negeri 4 Halmahera utara Pada Materi Memahami Permasalahan Ekonomi - Usman Amiruddin (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to improve student learning outcomes in economic subjects material economic problems. It is necessary to create a learning condition that allows active participatory students so that they can understand the material in a meaningful way. In this research, the research method used is Classroom Action Research (CAR). The results showed that the Word Square learning model could improve student learning outcomes, especially the economic problem material from the second cycle, an increase compared to the first cycle, namely 19 students had a sufficient score in accordance with the standard of learning completeness with an average value of 81.0. % compared to the first cycle with an average value of 68.9%. With the above results, it can be concluded that based on the results of research conducted in cycle I and cycle II using the Word Square learning model, students have achieved mastery learning, but there has been an increase from the results of 68.9% in the first cycle to 81.0% in the first cycle. cycle II so as to improve student learning outcomes.